A cross-sectional study among Polish hunters: seroprevalence of hepatitis E and the analysis of factors contributing to HEV infections - Baumann-Popczyk, Anna (Med Microbiol Immunol, 2017)
Hepatitis E virus (HEV) is known as zoonotic agent. The main reservoirs of HEV in Europe are pigs, wild boars, and deer. Hunting activity is considered to be a risk factor for HEV infection. We conducted a cross-sectional study among 1021 Polish hunters. To understand socio-demographic characteristics of this population and to gather information on potential exposures, all participants completed a questionnaire. Commercial immunoassays were employed to estimate seroprevalence anti-HEV. Samples with confirmed positive result of anti-HEV IgM were examined for HEV RNA. Anti-HEV IgG were identified in 227 people, 22.2% of the studied group. Seroprevalence among the studied hunters was associated with age ≥65 [adjusted prevalence ratio (aPR) 1.6, p = 0.037), living in a house (aPR 1.54, p = 0.013), professional contact with farm animals (aPR 1.09, p = 0.01), and consumption of stewed offal (aPR 1.61, p = 0.00). Washing hands after disembowelment was linked to lower seroprevalence (aPR 0.53; p = 0.00). Lower prevalence of anti-HEV IgG among hunters living in cities was associated with age: 35–49 (aPR 0.52, p = 0.011) and 50–64 (aPR 0.93, p = 0.58), living in a house (aPR 1.58, p = 0.002) and owning a cat (aPR 0.58, p = 0.042). Among hunters living in rural areas, seropositivity was associated with contact with farm animals (aPR 1.66, p = 0.013) and consumption of stewed offal (aPR 1.81; p = 0.001). Contrary to initial assumptions, it was concluded that hunting was of significantly lesser importance than other factors. Due to the high level of HEV seroprevalence identified, we recommend conducting a large-scale study in the general population of Poland.